ВЛИЯНИЕ СПЕЦИАЛЬНОСТИ НА СТРУКТУРУ ЯЗЫКОВОЙ КАРТИНЫ МИРА (Philological Studies, 2019)
The article deals with the experimental study of the factor “occupation” influence on the structure of the language worldview. The research is based on the material of component semantic analysis of “naive” definitions of borrowed words, used extensively in the media. The analysis of data shows that occupation effects on the variability of the words meanings, that icon the structure of the language worldview. Differences in worldview affect mainly in detailing the fragments of reality that is more important to some occupation, as well as the nature of the detail values.